2017
DOI: 10.1590/1677-5449.002617
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lower extremity blood flow during advancing phases of pregnancy and the effects of special footwear

Abstract: Background During pregnancy, a number of changes affecting venous blood flow occur in the circulatory system, such as reduced vein wall tension or increased exposure to collagen fibers. These factors may cause blood stagnation, swelling of the legs, or endothelial damage and consequently lead to development of venous disease. Objectives The aim of this study is to evaluate the effect of special footwear designed to improve blood circulation in the feet on venous blood flow changes observed during advancing pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Also, one study compared the effects of massage with grape seed oil with sweet almond oil. In terms of analyzed outcomes, there were substantial differences between the assessed trials (9,(21)(22)(23)(24)(25)(26). The trials had a high risk of performance and detection bias and were essentially unclear for selection bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, one study compared the effects of massage with grape seed oil with sweet almond oil. In terms of analyzed outcomes, there were substantial differences between the assessed trials (9,(21)(22)(23)(24)(25)(26). The trials had a high risk of performance and detection bias and were essentially unclear for selection bias.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the experimental study showed that wearing the tested footwear could prevent venous blood velocity from lowering during the later stages of pregnancy. Nonetheless, more research is required on the beneficial effects of using the footwear on venous flow and its application (23). 2011) evaluated the effect of water immersion on reducing peripheral edema in the last six weeks of pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…Tested footwear and insoles J Hanák R (Snovídky, Czech Republic) are designed to help with redistribution of forces acting on foot. The insoles, US Patent US 20150013189 A1, most prominent features are a depression under the first metatarsophalangeal joint, elastic leather straps, which are sewn into the shoe upper sole at the instep and the heel, and a depression under the heel [17][18][19]. The tested footwear and insoles (Fig 1) were obtained from the producer Boty J Hanák R, s.r.o., shoe type Active, high top Active and sandal shoes type 304.…”
Section: Methodsmentioning
confidence: 99%
“…The condition was that they had to wear shoes every day. Patented J Hanák R biomechanical footwear and insoles are designed to help with redistribution of forces acting on foot, to support both longitudinal and transverse arches of the foot and to strengthen the foot muscles during movement (Gimunová et al, 2017;Hanák & Zvonař, 2013). Experimentally these shoes are given to pregnant women to detection changes of plantar pressure characteristics and foot characteristics during the last trimester.…”
Section: Methodsmentioning
confidence: 99%